Divorce, domestic violence, and help seeking - Elena Pisanelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2024)
This paper examines the impact of the 2014 Italian divorce law on help-seeking behavior of domestic violence victims and femicides. I find that contrary to expectations, the reform, which aimed to make divorce cheaper while requiring mutual consent, led to a decrease in help-seeking behavior among intimate partner violence (IPV) survivors and an increase in femicides perpetrated by husbands. These findings suggest that while reducing the cost of divorce may empower individuals to leave abusive relationships, the requirement for mutual consent may inadvertently escalate violence as husbands seek to assert control and prevent separation. The study underscores the importance of considering the unintended consequences of divorce legislation and prioritizing the safety of IPV survivors in family policy interventions.
Keywords: J12; J16; I10; I31; 330; Domestic violence; Femicides; Divorce; Help-seeking; Family policy